Towards Targeting the Aryl Hydrocarbon Receptor in Cystic Fibrosis. (18th February 2018) - Puccetti, Matteo; Paolicelli, Giuseppe; Oikonomou, Vasileios; De Luca, Antonella; Renga, Giorgia; Borghi, Monica; Pariano, Marilena; Stincardini, Claudia; Scaringi, Lucia; Giovagnoli, Stefano; Ricci, Maurizio; Romani, Luigina; et al.
Abstract : Tryptophan (trp) metabolism is an important regulatory component of gut mucosal homeostasis and the microbiome. Metabolic pathways targeting the trp can lead to a myriad of metabolites, of both host and microbial origins, some of which act as endogenous low-affinity ligands for the aryl hydrocarbon receptor (AhR), a cytosolic, ligand-operated transcription factor that is involved in many biological processes, including development, cellular differentiation and proliferation, xenobiotic metabolism, and the immune response. Low-level activation of AhR by endogenous ligands is beneficial in the maintenance of immune health and intestinal homeostasis. We have defined a functional node whereby certain bacteria species contribute to host/microbial symbiosis and mucosal homeostasis. A microbial trp metabolic pathway leading to the production of indole-3-aldehyde (3-IAld) by lactobacilli provided epithelial protection while inducing antifungal resistance via the AhR/IL-22 axis. In this review, we highlight the role of AhR in inflammatory lung diseases and discuss the possible therapeutic use of AhR ligands in cystic fibrosis.